Booster seats for child passengers: lessons for increasing their use. Issue 3 (1st September 2001) - Rivara, F P; Bennett, E; Crispin, B; Kruger, K; Ebel, B; Sarewitz, A
Abstract : Objective— To explore parental knowledge, attitudes, beliefs, and barriers to use of booster seats in cars for 4–8 year old children. Methods— Three focus groups conducted by a professional marketing firm. Results— Many parents were confused about the appropriate weight and age of children who should be in booster seats; most parents incorrectly identified the age at which it was safe to use a lap-shoulder belt. Legislation was viewed as a positive factor in encouraging use. Cost of seats was frequently cited as a barrier to ownership, as were child resistance, peer pressure from older children, the need to accommodate other children in the vehicle, and the belief that a lap belt was adequate. Messages from health care providers, emergency medical services, or law enforcement personnel were believed to be most effective. Conclusion— Campaigns to promote booster seat use should address issues of knowledge about appropriate age and size of the child, cost, inadequacy of lap belts, and resistance to use by the child.